PRINSIP-PRINSIP PEMBELAJARAN DALAM ISLAM - Abd. Mukti (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2008)
Abstact: The Principles of Learning in Islam. The present condition of Islamic education betrays its classical golden age, when Islam developed highly sophisticated system of education. The present ineffectiveness and inefficiency of Islamic learning was resulted partly from poor quality of learning system. The present author tries to extract from past experiences of Muslim some of the most important learning principles, believing that they can be reintroduced into the present Islamic education activities. The author argues that despite the fact that they were products of past time, they can still be relevant for the present time. Kata Kunci: prinsip, pembelajaran, Islam